N-nitrosodimethylamine reduction by Lactobacillus pentosus R3 in fermented cooked sausages. (June 2021) - Shao, Xuefei; Zhu, Miaomiao; Zhang, Ziye; Huang, Pan; Xu, Baocai; Chen, Conggui; Li, Peijun
Abstract: This study investigated the effects of Lactobacillus pentosus R3 on N -nitrosodimethylamine (NDMA) in the production and cooking of fermented sausages. L. pentosus significantly decreased the content of NDMA in fermented sausages, especially after the ripening and cooking steps ( P  < 0.05). Dimethylamine and carbonyl content, thiobarbituric acid reactive substances value, and content of non-haem iron of the sausages inoculated with L. pentosus were significantly lower than those of the control ( P  < 0.05). It means that L. pentosus may decrease NDMA content in the sausages through direct degradation, indirect reduction of its precursors, weakened oxidation, and a decrease in the non-haem iron content. In addition, the lower pH and water activity of the inoculated sample may also inhibit the formation of NDMA by improving the microbial quality of the sausages. Therefore, inoculating L. pentosus R3 into fermented cooked sausages is an effective way to reduce NDMA content. Highlights: Lactobacillus pentosus reduced N -nitrosodimethylamine in fermented cooked sausages. The reduction occurred during the ripening and cooking of the sausages. L. pentosus inhibited lipid and protein oxidation in the sausages. L. pentosus decreased the non-haem iron content in the sausages. L. pentosus improved the safety of the sausages.